America's Water Infrastructure Act: Considerations for Small Systems. Issue 11 (4th November 2020) - Strother, Britta
Abstract : America's Water Infrastructure Act (AWIA) of 2018 serves as a catalyst for utilities to evaluate their resilience to risk and to create emergency plans for responding to any unfortunate situations. AWIA gives utilities significant latitude for how they respond but requires small utilities to create a risk and resilience assessment by June 30, 2021, and an emergency response plan by Dec. 30, 2021.